Methyl jasmonate-induced emission of biogenic volatiles is biphasic in cucumber a high-resolution analysis of dose dependence - Jiang, Yifan (Journal of experimental botany, 2017)
© The Author 2017. Published by Oxford University Press on behalf of the Society for Experimental Biology.